Multimodal intervention to improve the transition of patients with inflammatory bowel disease from pediatric to adult care: protocol for a randomized controlled trial - Bollegala, Natasha; Barwick, Melanie; Fu, Nancy; Griffiths, Anne M.; Keefer, Laurie; Kohut, Sara A.; Kroeker, Karen I.; Lawrence, Sally; Lee, Kate; Mack, David R.; Walters, Thomas D.; de Guzman, Jacqueline; et al. (Université d'Ottawa | University of Ottawa, 2022)
Abstract Background Transition in care is defined as the “purposeful and planned movement of adolescents and young adults with a chronic medical condition from pediatric to adult-oriented healthcare systems/care providers.” Currently, there are no Level 1 evidence-based interventions to improve the care of transitioning adolescents and young adults (AYAs) with inflammatory bowel disease (IBD). The development of a transition program using a biopsychosocial approach will improve the standards for healthcare delivery to transitioning IBD patients. This is a protocol for a structured randomized controlled trial (RCT) to assess the clinical and implementation effectiveness of a multimodal intervention focused on improving patient function, transition readiness and outcomes among AYA patients with IBD being cared for at pediatric centers in Canada. Methods This multi-center RCT is a type 1 hybrid effectiveness-implementation trial to evaluate effectiveness of the intervention and how it can be implemented more widely after the trial. We will include patients aged 16.0–17.5 years. The intervention program consists of 4 core components: (1) individualized assessment, (2) transition navigator, (3) virtual patient skills-building with a focus on building resilience, self-management and self-efficacy, and (4) a virtual structured education program. The control group will undergo standard-of-care defined by each participating center. The primary outcome will be the IBD Disability Index, a validated measure to assess patient functioning. Secondary outcomes include transition readiness and success, anxiety and depression scales, and health service utilization rates. Additionally, we will measure implementation outcomes and related barriers and facilitators for the intervention program. Discussion The type 1 hybrid effectiveness-implementation design will allow for the development of a feasible, sustainable, and acceptable final intervention model. The intervention will consist of modules that can be accessed in an online, virtual platform. The implementation will allow centralization of interventions and funding in order to minimize the impact on local clinical practice or hospital resources. The authors anticipate that the main study limitation will relate to study subjects not completely adhering to every component of the intervention, which will be evaluated and addressed using the implementation science approach. Trial registration NCT05221281. Registry: ClinicalTrials.gov. Date of registration: February 2, 2022. https://clinicaltrials.gov/ct2/show/NCT05221281 .